Corporate taxation, tax administration and financial development - Mardan, Mohammed (CESifo, Center for Economic Studies & Ifo Institute, 2019)
This paper analyzes corporate tax-related policies and the difference between them in developed and developing countries. I show that the relationship between financial development and corporate income tax rates as well as the tax administrations' effectiveness follows a U-shaped pattern, a discrepancy to the observation that developing countries usually have the weakest administrative structures. However, this observation can be explained under the premise that the tax administration's effectiveness is determined at a later stage, and not simultaneously with the corporate tax rate. Moreover, I show that, under this premise, fighting tax havens increases tax revenues in developed countries, but decreases them in developing countries. Instead, if policies are simultaneously considered, the fight against tax havens will also benefit developing countries.
10419/214942
Keywords: Graue Literatur; developing countries; profit shifting; tax administration; tax competition; tax haven